Legal Damages for Losses of Chances - Urs Schweizer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
This paper deals with legal damages if losses of chances are at stake. In response to disparate ad hoc rules that have emerged from legal practice in Europe, the present paper proposes a unifying principle to handle such cases. Quite generally, the purpose of a damages award is to compensate the claimant and should be based on the difference in value between due performance and actual performance. To cope with limited observability, it is suggested to still award the difference though on average over the observed event. The paper calculates damages in line with this general principle. The proposed damage scheme is shown to fully compensate the victim and to provide efficient incentives for precaution, be it that multiple injurers act non-cooperatively or in concert, even if losses of chances are at stake.
urn:nbn:de:bvb:19-epub-13317-0
Keywords: K12; K13; D62; 330; estimating legal damages; liability for torts; liability for breach of contracts; uncertain causation; difference hypothesis